2022
DOI: 10.48550/arxiv.2204.09692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Age of Discovery with the James Webb: Excavating the Spectral Signatures of the First Massive Black Holes

Kohei Inayoshi,
Masafusa Onoue,
Yuma Sugahara
et al.

Abstract: The James Webb Space Telescope (JWST) will open a new window of the most distant universe and unveil the early growth of supermassive black holes (BHs) in the first galaxies. In preparation for deep JWST imaging surveys, it is crucial to understand the color selection of high-redshift accreting seed BHs. We model the spectral energy distribution of super-Eddington accreting BHs with millions of solar masses in metal-poor galaxies at z 8, applying post-process line transfer calculations to radiation hydrodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Once the conditions for super-Eddington mass accretion are satisfied, the central BH becomes a milli-QSO radiating with 𝐿 bol 𝐿 Edd 4×10 42 erg s −1 (𝑀 • /3×10 4 M ). While the IMBH in the MMH halo located at 𝑧 ∼ 15 would be too faint to be observed, more luminous milli-QSOs with 𝐿 bol ∼ 10 45 erg s −1 , resulting from higher BH mass 𝑀 • 10 6 M and/or extremely high-Eddington ratios reach the detection limit for upcoming observations by the James Webb Space Telescope (Inayoshi et al 2022a). A future discovery of such milli-QSOs at 𝑧 > 10 will be strong evidence of IMBH formation in the primordial universe and its rapid mass growth to establish SMBH populations found at 𝑧 ∼ 7.…”
Section: Subsequent Mass Growth Of Remnant Bhsmentioning
confidence: 89%
“…Once the conditions for super-Eddington mass accretion are satisfied, the central BH becomes a milli-QSO radiating with 𝐿 bol 𝐿 Edd 4×10 42 erg s −1 (𝑀 • /3×10 4 M ). While the IMBH in the MMH halo located at 𝑧 ∼ 15 would be too faint to be observed, more luminous milli-QSOs with 𝐿 bol ∼ 10 45 erg s −1 , resulting from higher BH mass 𝑀 • 10 6 M and/or extremely high-Eddington ratios reach the detection limit for upcoming observations by the James Webb Space Telescope (Inayoshi et al 2022a). A future discovery of such milli-QSOs at 𝑧 > 10 will be strong evidence of IMBH formation in the primordial universe and its rapid mass growth to establish SMBH populations found at 𝑧 ∼ 7.…”
Section: Subsequent Mass Growth Of Remnant Bhsmentioning
confidence: 89%
“…The spectra found in Pacucci et al (2015) have a steep slope in the infrared, due to radiation from the DCBH being reprocessed at lower energies by intervening matter (Pacucci et al 2016). Inayoshi et al (2022a) have recently found that Balmer lines for black holes accreting at super-Eddington rates are ∼ 2 − 7 times stronger than in low-𝑧 quasars. This is because the gas is denser and has a larger column density around these DCBHs than in a usual thin disk, and so excitation from 𝑛=2 (populated by trapped Ly𝛼) to 𝑛 ≥ 3 states (via collisions) is more common.…”
Section: Mass Relation Vs Other Detection Methodsmentioning
confidence: 99%